Relationship between Parents Educational Degree and Family Economy Status with Adolescentâs Sexual Behaviour in SMA Negeri 2 Surakarta - Wibisono, Zuhud Nur; Yuliadi, Istar; Suwito, Djoko (Nexus Kedokteran Komunitas, 2017)
Background: Adolescent in Indonesia are currently undergoing social changes from traditional society to modern society. This condition Â may trigger adolescent to develop a bad behavior, for example bad sexual behavior if accompanied by bad influences such as permissiveÂ  environment or mass media. There are multiple factors that can influence adolescent behavior. Family, in this case parents educational degree and family economy status are thought to have great influence in adolescent behavior. Methods: This research was analytic observational research using Â survey methods with cross sectional design. Stratified cluster random sampling was used for sampling methods. The samples are 103 students from class X, XI, and XII. Data were obtained from questionnaire that has already validated. The data were analyzed using Spearman statistical analysis with Statistical Product and Service Solution (SPSS) 17 for Windows. There are two variables, parents educational degree (low, middle and high category) and family economy status (low, middle, high). Results: There are 103 respondents which consist of 81 good sexual activity respondent and 22 bad sexual activity respondent. Spearman and Kendall-tau show that correlation coefficients between adolescent sexual activityÂ  with parents educational degree areÂ  0.442 and 0.431, respectively (p value <0.001), whereas correlation coefficients between adolescent sexual activity with family economy status are 0.338 and 0.329, respectively (p value <0.001). Conclusions: It can be concluded that there is significant association between parents educational degree and family economy status with adolescentâs sexual behavior.Correlation coefficient are positive, that is the higher educational degree or family economy status, the higher possibility the adolescent to do a bad sexual activity. Keywords: Parentsâ educational degree, family economy status, adolescentâs sexual behavior.Â